(untitled) (World Economics and Finance Bulletin, 2026)
The concept of a green economy encompasses scientific ideas of economics such as resource-saving economy, ecological economics, environmental economics, green policy, the theory of international economic relations, economic modernization, and innovative economy. The green economy considers green transport and the transport infrastructure that creates the conditions for its functioning as one of the system-forming sectors of the regional economy, ensuring the territorial integrity of regions and the unity of their economic space. Therefore, the development of transport infrastructure is a necessary condition for implementing an innovative model of economic growth and improving the quality of life of the population in the region. In the article, the author describes the socio-economic significance and theoretical approaches to the development of transport service infrastructure in the context of a green economy.